Pemanfaatan Buah Sukun di Maluku menjadi Tepung Sukun - Mailoa, Meitycorfrida; Lopulalan, Chintya G C; Nurlette, Siti A (Tropical Small Island Agriculture Management, 2023)
Breadfruit can be used as a wheat flour substitute and processed into breadfruit flour. Breadfruit in Maluku tends to have different physical conditions and flavors depending on its location or area of origin. This study aims to process breadfruit from various growing regions of Maluku into breadfruit flour, followed by a sensory test to determine consumer preference levels and the hedonic quality of the flour. This study uses a completely randomized design with one factor: the breadfruit's location. The results of the study show that the aroma (2.72-2.88/somewhat liked and has a breadfruit aroma), texture (2.95-3.32/somewhat liked to liked and has a somewhat smooth to smooth texture), and color (2.60-3.29/somewhat liked to liked and has a yellow-brown to white-yellow color). Breadfruit flour from Latuhalat village has a higher preference level than the other two flour types.